Self-Disgust Is Associated With Loneliness, Mental Health Difficulties, and Eye-Gaze Avoidance in War Veterans With PTSD - Ypsilanti, Antonia; Gettings, Richard; Lazuras, Lambros; Robson, Anna; Powell, Philip A.; Overton, Paul G. (Frontiers in Psychology, 2020)
In the present study we examined, for the first time, the association between self-disgust, loneliness and mental health difficulties in war veterans diagnosed with PTSD. For this purpose we used a mixed methods design, incorporating surveys and a novel eye-tracking paradigm, and compared the findings from the PTSD veteran group (n = 19) to those from a general population group (n = 22). Our results showed that the PTSD veteran group reported almost three times higher scores in self-disgust, and significantly higher scores in loneliness and mental health difficulties (anxiety and depression), compared to the general population. Furthermore, self-disgust mediated the association between loneliness and anxiety symptoms in both groups. The results from the eye-tracking paradigm further showed that veterans with PTSD displayed a self-avoidance gaze pattern, by looking significantly more towards pictures of faces of unknown others and away from their own face - a pattern that was not replicated in the general population group. Higher self-disgust scores were significantly associated with longer total gaze to the pictures of others (vs. the self). Our findings have implications for the role of self-disgust in the mental health of war veterans.